2009
DOI: 10.1111/j.1463-1326.2009.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐GLP‐1, a novel long‐lasting glucagon‐like peptide‐1 polymer, ameliorates hyperglycaemia by improving insulin sensitivity and increasing pancreatic beta‐cell proliferation

Abstract: Our results indicated that Poly-GLP-1, a novel GLP-1 polymer, has long-lasting and potent effects on glycaemic control in vivo, and these beneficial effects may be because of improvement of insulin sensitivity and promotion of islet growth and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…[22][23][24][25] A recent study in pigs showed increased islet number and β-cell proliferation after RYGBP, in parallel with a rise in GLP-1, demonstrating the effect of RYGBP on the plasticity of the endocrine pancreas in this animal model. 43 Whether this is true in humans is unknown.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] A recent study in pigs showed increased islet number and β-cell proliferation after RYGBP, in parallel with a rise in GLP-1, demonstrating the effect of RYGBP on the plasticity of the endocrine pancreas in this animal model. 43 Whether this is true in humans is unknown.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 99%
“…21 Both GLP-1 and GIP have a trophic effect on the β-cell, as demonstrated in vitro and in vivo in rodent studies. [22][23][24][25] GLP-1 has other important physiological effects, including potentiation of GSIS in the post-prandial setting, suppression of glucagon, slowing of gastric emptying, decrease of body weight and favorable cardiovascular protection, 1,26 that makes it an attractive tool for the treatment of overweight or obese individuals with diabetes. The half-life of GLP-1 and GIP is only few minutes and both incretins are rapidly inactivated by the enzyme dipeptidyl peptidase 4 (DPP-4).…”
Section: Importance Of the Incretin Effect In Physiologymentioning
confidence: 99%
“…Recombinant DNA technology is also of interest for the synthesis of tandem repeats of naturally occurring peptides, as a strategy for the high-yield synthesis of peptide drugs and antigens 610. Furthermore, polymerization of peptide drugs with intervening protease cleavable sequences has the potential to improve their pharmacokinetics and drug efficacy11,12. However, current methods for the polymerization of DNA suffer from one or more critical limitations: they (1) require numerous steps, (2) are difficult to parallelize, and (3) do not provide tunable control over a range of molecular weights, all of which greatly limit the ability to simultaneously synthesize multiple variants with a range of repeat units and compositions.…”
mentioning
confidence: 99%
“…An emerging strategy for temporally sustained peptide delivery involves peptide polymerization with intervening protease-cleavable linkers 11. However, as existing designs employed protease sites that are rapidly cleaved, these constructs still required repeated daily injections.…”
mentioning
confidence: 99%
“…A long chain polymer of GLP-1 that is slowly degraded in the circulation by endopeptidases is at an early stage of testing. 15 Delivery of GLP-1 analogues by buccal, oral, and nasal routes and dermal patches, rather than injections, is being investigated.…”
Section: Other Glp-1 Based Treatmentsmentioning
confidence: 99%